Thermal diffusivity of carbon pellets (CPs) treated with KOH - Haydari, Mehdi; Abd. Moksin, Mohd Maarof; Abdelrahman, Abubakar Elshiekh; Deraman, Mohamad; Mat Yunus, Wan Mahmood; Grozescu, Ionel Valeriu (Science Publications, 2008)
In this work thermal diffusivity of carbon pellets (CPs) treated with different percentage level of KOH has been studied. Thermal diffusivity measurements were carried out at room temperature by using photoflash technique. The technique consists of a camera flash having approximately 5 ms pulse duration for heating and a thin film of polyvinylidene difluoride (PVDF) attached to the back of the samples for signal detection. Eight carbon samples treated with different percentage level of KOH (0 to 7 mole percent) were studied and the thermal diffusivity result was compared with SEM which showed that the sample with highest thermal diffusivity had distinctly lower porosity and better grain alignment.